A study on correlation between acanthosis nigricans (an) and polycystic ovary syndrome (pcos) in indian adolescent girls - BIJAY KHAN; RANJAN BASU (International Journal of Pharma and Bio Sciences, 2017)
Acanthosis nigricans (AN) is a readily recognizable dermatological manifestation of an underlying metabolic defect like insulin resistance (IR) or obesity which is closely associated with polycystic ovarian syndrome (PCOS). The aim of the study was to compare the clinical and biochemical parameters of Indian adolescent girls with PCOS with and without AN. 58 adolescent girls in the age group of 14-19 years with the complaints of oligomenorrhoea (≤ six menses per year) with clinical evidences of hyperandrogenism (hirsutism and/ or acne) were studied. In each case clinical parameters like body mass index (BMI) (as kg / m 2) from height and weight measurements, abdominal circumference (AC), blood pressure (BP), hirsutism score, presence of acne and acanthosis (AN) were noted. Biochemical tests included the estimation of serum total testosterone (TT) and sex hormone binding globulin (SHBG) levels. Plasma insulin (PPI) and plasma glucose (PPG) levels. The study group was divided into two, based on the presence or absence of acanthosis nigricans. Significant differences were found in the parameters of BMI (p=0.0001), AC (p=0.0001); DBP (p= 0.01); TT (p= 0.002); FAI (p=0.002) between the two groups. The model signifies positive impacts of BMI, testosterone level, PP insulin level and negative influence of PP sugar, SHBG levels on AN.. AN in adolescent girl with PCOS is another clinical marker of obesity. This study shows that presence of AN is not an indicator of underlying insulin resistance or glucose intolerance.